Chromosomal damage in fish (Anguilla anguilla L.) induced by the fungicide Macozan® upon exposure and post-exposure periods - Crespo, Rodrigo Dinis (2017)
Mancozan® is a dithiocarbamate fungicide used worldwide and its consumption has been increasing year after year. Due to its extensive use, their metabolites can be easily found in aquatic ecosystems around the world, representing thus a potential hazard to non-target organisms. Many studies performed with its active ingredient, mancozeb, have demonstrated its negative impact to fish. However, the toxic effects, and particularly the genotoxic potential of the commercial formulation Mancozan® are still poorly understood. Thus, and in order to improve the knowledge concerning this thematic, the present study aimed to evaluate the genotoxic potential of the fungicide Mancozan® to blood cells of the European eel (Anguilla anguilla) following a short-term (3 days) exposure to environmental realistic concentrations (2.8 and 28 μg.L-1). With the intuit of investigate the damage progression after the contamination source cessation, a post-exposure period (1, 7 and 14 days) was included, where fish were transferred to fungicide-free water. In order to evaluate the genetic damage, the ENA (erythrocytic nuclear abnormalities) assay was performed. Additionally, the frequency of immature erythrocytes (IE) was scored in order to provide indirect information on the erythrocyte catabolism and erythropoiesis rate. As a complement, the EMI (erythrocyte maturity index) was adopted in order to better discriminate the stage of erythrocytic immaturity. The obtained results demonstrated the potential of the highest concentration of Mancozan® to induce chromosomal damage, following a 3 days exposure, as well as a rapid recover in the post-exposure period. On the other hand, the lowest concentration of the commercial formulation was able to induce chromosomal damage only 14 days after the end of the exposure period, suggesting a progressive degradation and the collapse of eel erythrocytes defences. At the same time it was observed, through the IE assay and the calculation of the EMI, that the balance between the erythropoiesis, erythrocytes elimination and the cellular maturation rate was not affected by the exposure to the fungicide and consequently had no influence in the appearance of ENA. Globally, these results reinforce the idea concerning the pesticide risks to non-target organisms, highlighting the occurrence of a short-term genome-destabilizing in fish, as a result of occasional pesticide applications.